The Study of 3D Simulation on Heat Transfer Enhancement on Fin Tube Heat Exchanger Using Delta Wing and Winglet Vortex Generators - Mardikus, Stefan; Putri, Claudia Agata; Seen, Michael; Rines, Rines; Lukiyanto, Y. B.; Purwadianto, Doddy; Winarbawa, Heryoga; Dyaksa, Gilang Argya; Kusbandono, Wibowo (Universitas Sanata Dharma, 2024)
The vortex generator is one of the methods to improve heat transfer augmentation on flow characteristics in the air side of the fin and tube heat exchanger. There are some models of vortex generators to produce longitudinal vortices when the airflow passes the surface of the vortex generator. In the previous studies, the longitudinal vortices were able to reduce the wake region phenomenon behind the tube heat exchanger. This research aims to investigate the thermal performance of heat transfer on the collaboration between two models of vortex generators namely delta wing and winglet vortex generators on plate fin and tube heat exchanger. The simulation used four models (1) without the vortex generator (2) with the delta wing vortex generators (3) with delta winglet (4) with the combination of delta wing and winglet. The study was generated with computational fluid dynamics. The boundary conditions were set in the inlet as velocity and the outlet as pressure outlet. The airflow of velocity is represented by Reynolds numbers in the range of 4000 - 8000 with an interval of 500. The wall temperature of the tube is given at 400 Kelvin and the temperature of the airflow is given at 300 Kelvin. The epsilon model was used in the turbulence model of the simulation. The result explained that the thermal performance of heat transfer on delta winglets improved the airflow to induce longitudinal vortices and then reduced the wake region to improve the heat transfer coefficient more than other vortex generator models